THE UNIQUE CHARACTERISTICS OF THE ENGLISH LANGUAGE A COMPREHENSIVE ANALYSIS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
English, being one of the most widely spoken and written languages globally, holds a prestigious position as an international language. This article explores the historical, political, and economic factors contributing to the widespread popularity of English. Through an examination of its characteristics, including receptiveness, heterogeneousness, fixed word order, use of periphrases, and the development of intonation, we delve into the reasons behind the phenomenal growth and success of the English language. Each characteristic is dissected to highlight its impact on the language's evolution and usage. Furthermore, the article discusses how these qualities, while not all inherently positive, have collectively shaped English into a language that is both versatile and challenging to master, as noted by C.L. Wren.